﻿A current insight and future perspective of edible bird nest as caviar of the east - Muhammad Andika Haraharap; Osfar Sjofjan; Lilik Eka Radiati; Muhammad Halim Natsir; Rony Abdi Syahputra; Fahrul Nurkolis (Pensoft Publishers, 2023)
Edible bird's nest (EBN) is a highly valuable food product obtained from swiftlet nests, primarily those of the Aerodramus genus. Due to its purported health benefits and exceptional taste, EBN is often referred to as the "caviar of the East." This abstract presents a comprehensive review of the current state of EBN research, focusing on its chemical composition, nutritional value, pharmacological effects, and safety considerations. The chemical composition of EBN is intricate and influenced by various factors, including bird species, geographic origin, nest collection time, and processing methods. It is primarily composed of proteins, polysaccharides, minerals, lipids, and a wide range of bioactive compounds such as sialic acid, amino acids, and antioxidants. Additionally, EBN has demonstrated antioxidant, anti-inflammatory, anti-tumor, and anti-aging properties attributed to these bioactive constituents. While EBN is generally considered safe for human consumption, it is essential to address concerns related to potential contaminants like heavy metals, microbial pathogens, and allergens. This review offers a comprehensive overview of previous research conducted on residual impurities that may be present in edible bird's nests (EBNs). The review encompasses various aspects, including, the regulatory framework and associated concerns regarding EBNs, the levels of nitrite and nitrate detected in EBNs, the presence of bacteria, fungi, and mites in EBNs, the identification of allergenic substances in EBNs, and the presence of heavy metals and excessive mineral content at different stages of EBN processing, including raw uncleaned (RUC) EBNs, raw cleaned (RC) EBNs, and EBNs after undergoing treatment. Graphical abstract: